The activation domain of a basic helix-loop-helix protein is masked by repressor interaction with domains distinct from that required for transcription regulation. - Jayaraman, P S (1994)
While there are many examples of protein-protein interactions modulating the DNA-binding activity of transcription factors, little is known of the molecular mechanisms underlying the regulation of the transcription activation function. Using a two-hybrid system we show here that transcription repression of the basic domain/helix-loop-helix factor PHO4 is mediated by complex formation with the PHO80 repressor. In contrast to other systems, such as inhibition of GAL4 by GAL80 or of p53 by MDM2, where repression is mediated by direct interaction at regions overlapping the transcription activation domain, interaction with PHO80 involves two regions of PHO4 distinct from those involved in transcription activation or DNA-binding and dimerization. The possibility that repression of PHO4 by PHO80 may represent a general mechanism of transcription control, including regulation of the cell-type-specific transcription activation domain of c-Jun, is discussed.